Information and Business Intelligence International Conference, IBI 2011, Chongqing, China, December 23-25, 2011. Proceedings, Part II - Qu, Xilong; Yang, Yuhang; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This two-volume set (CCIS 267 and CCIS 268) constitutes the refereed proceedings of the International Conference on Information and Business Intelligence, IBI 2011, held in Chongqing, China, in December 2011. The 229 full papers presented were carefully reviewed and selected from 745 submissions. The papers address topics such as communication systems; accounting and agribusiness; information education and educational technology; manufacturing engineering; multimedia convergence; security and trust computing; business teaching and education; international business and marketing; economics and finance; and control systems and digital convergence.
Keywords: Computer science; Computer Communication Networks; Computer software; Database management; Information storage and retrieval systems; Artificial intelligence; Computer Science; Artificial Intelligence (incl. Robotics).; Information Systems Applications (incl. Internet).; Computer Communication Networks; Information Storage and Retrieval; Algorithm Analysis and Problem Complexity; Database Management